SISTEM INFORMASI AKADEMIK SISWA BERBASIS WEBSITE PADA SMAN 1 NGABANG - Setiawan Susanto, Ari; Dewayani, Ery; Sutrisno, Tri (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
Information system for Sman 1 Ngabang to process academic of students this web-based and mobile web system can help schools in learning features. The web- based is well designed using the PHP programming language and for the database using MySQL and phpMyAdmin. For testing using the white box method. The method used in software development is Rapid Application Development. The results obtained are Sman 1 Ngabang uses a web-based to obtain information system data in the form of reports. Admin also has full data access to add, update, and delete existing data in the database.